Organization of Primary Seeding of Pumpkin (Cucurbita Pepo L.) Orbita Variety - Sirojiddin Turdikulovich Juraev; Rano Alisherovna Rakhmatullayeva (Web of Journals Publishing, 2023)
Tthe article deals with the establishment of primary seed production of the Orbit variety of pumpkin (cucurbita pepo l.).
Keywords: pumpkin, orbit variety, seed production, fruit, productivity, cultivation, crop.